Neutron studies on the conversion of the RA-3 Reactor LEU fuel - Babinó, J.; Madariaga, M.; Testoni, Jorge Eduardo (Comisión Nacional de Energía Atómica; Argentina, 1980)
Fil: Babinó, J. Comisión Nacional de Energía Atómica; Argentina